2012
DOI: 10.1002/pmic.201100465
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of spontaneous mutants of Lactococcus lactis: Involvement of GAPDH and arginine deiminase pathway in H2O2 resistance

Abstract: Lactococcus lactis, one of the most commonly used dairy starters, is often subjected to oxidative stress in cheese manufacturing. A comparative proteomic analysis was performed to identify the molecular modifications responsible for the robustness of three spontaneous H(2)O(2)-resistant (SpOx) strains. In the parental strain, glyceraldehyde-3-phosphate deshydrogenase (GAPDH) activity is ensured by GapB and the second GAPDH GapA is not produced in standard growth conditions. We showed that GapA was overproduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…In Tn mutants with an upregulated ADI operon, tolerance of the Sod-deficient strain was partially restored. These results seem to support the above-mentioned oxidative-stress-based killing model, since a recent study demonstrated the direct implication of the ADI operon in the oxidative stress response of Lactococcus lactis (34). In a spontaneously H 2 O 2 -resistant mutant of this species, the ADI operon was found to be upregulated and disruption of the first (arcA) or second (arcB) gene of this operon abolished peroxide resistance.…”
supporting
confidence: 56%
“…In Tn mutants with an upregulated ADI operon, tolerance of the Sod-deficient strain was partially restored. These results seem to support the above-mentioned oxidative-stress-based killing model, since a recent study demonstrated the direct implication of the ADI operon in the oxidative stress response of Lactococcus lactis (34). In a spontaneously H 2 O 2 -resistant mutant of this species, the ADI operon was found to be upregulated and disruption of the first (arcA) or second (arcB) gene of this operon abolished peroxide resistance.…”
supporting
confidence: 56%
“…The expression of sodA is also somewhat induced in vivo (+3.2-fold). Moreover, several other genes with known or suspected implications in oxidative stress are present in the in vivo induced gene database such as genes endoding thioredoxin reductase ( ef1405 ; +4.8-fold), two members of the ferric uptake regulator family, PerR ( ef1585 ; 4.4-fold) [ 52 ] and Fur ( ef1525 ; +5.9-fold), and the Dps family protein ( ef3233 ; +2.6-fold) [ 45 ] as well as the arc operon implicated in arginine metabolism ( ef0104-ef0108 , +7.9-fold) [ 53 ] and the sufCDSUB operon involved in the assembly of Fe-S clusters ( ef2390-ef2394 ; +7.4 fold)[ 54 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is responsible for the interconversion of 1,3-diphosphoglycerate and glyceraldehyde-3-phosphate, a central step in glycolysis and gluconeogenesis [55, 56]. The up-regulation of GAPDH in both two wheat cultivars can promote glucose metabolism to meet the increased substance and energy requirement for drought resistance as suggested by Rochat et al [57]. Triosephosphate isomerase (TPI) catalyzes the reversible interconversion of dihydroxyacetone phosphate and D-glyceraldehyde 3-phosphate, which is essential for efficient energy production in glycolysis [58].…”
Section: Discussionmentioning
confidence: 99%